2006
DOI: 10.1128/aac.00232-06
|View full text |Cite
|
Sign up to set email alerts
|

Successful Therapy of Experimental Endocarditis Caused by Vancomycin-Resistant Staphylococcus aureus with a Combination of Vancomycin and β-Lactam Antibiotics

Abstract: VRS1 is the first isolated strain of vancomycin-resistant Staphylococcus aureus (VRSA) found to carry the vanA gene complex previously described in Enterococcus. Under vancomycin pressure, VRS1 makes aberrant cell walls consisting of stem tetrapeptide and depsipeptide that lack the terminal D-Ala-D-Ala residues targeted by vancomycin. Previous data have suggested that this aberrant cell wall is not cross-linked by PBP2a, the enzyme responsible for cell wall transpeptidation in the presence of ␤-lactam antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 25 publications
3
33
0
3
Order By: Relevance
“…This concept is based on several in vitro and animal studies that demonstrated a synergistic effect of vancomycin-␤-lactam combinations against MRSA (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…This concept is based on several in vitro and animal studies that demonstrated a synergistic effect of vancomycin-␤-lactam combinations against MRSA (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…PBP 2a is not capable of cross-linking peptidoglycan containing stem peptide modified by the van genes (21,39). Although it is not universally seen, there are several observations that MRSA passaged in the presence of increasing concentrations of vancomycin has a decrease in oxacillin resistance or has a deleted mecA (1,36,41).…”
mentioning
confidence: 99%
“…Although uncommon in vivo (3), the seesaw effect was recently observed in a clinical VISA isolate with a retained mecA gene obtained during VAN therapy; of interest, after discontinuation of VAN therapy, the methicillin resistance phenotype was restored (32). Importantly, the combination of VAN and nafcillin has been shown to exert synergistic killing activities in vitro and in an experimental model of infective endocarditis (IE) (8) with both VISA and VRSA strains (14).…”
mentioning
confidence: 99%